Research Progress on Radiation Damage of Commonly Used Solid Lubricating Films - LI Jincheng, SHI Yeran, HUA Dongpeng, ZHOU Qing, XIA Qiaosheng, CHAI Liqiang, WANG Haifeng, WANG Peng (Cailiao Baohu)
Solid lubricating thin film materials play a significant role in aerospace，the nuclear industry and mechanical engineering due to their excellent performance in reducing friction and wear， as well as their good chemical stability and resistance to high temperatures.However，these materials face the challenge of radiation damage in extreme environments， such as space and high-temperature nuclear reactors， which can lead to a significant decrease in material performance， thus affecting their reliability and durability in practical applications.In this paper，three main types of solid lubricating thin films were first introduced， which included two-dimensional layered lubricating films， carbon-based lubricating thin films， and metal-based lubricating thin films.Two-dimensional layered lubricating films，such as graphene and transition metal dichalcogenides，showed ultra-low friction coefficients due to their single or few layers of atomic thickness， achieving a “superlubricating”effect.These materials were not only recognized for their excellent tribological properties but also for their exceptional mechanical strength and chemical inertness， making them potentially valuable for applications in harsh environments， such as nuclear radiation.Carbon-based lubricating thin films， such as hydrogenated amorphous carbon films， graphite， and fullerenes， maintained their lubricating performance in adverse environments due to their diverse allotropes of carbon and physical and chemical properties.Metal-based lubricating thin films， especially silver-based films， were shown to exhibit good lubricating performance in high-temperature and irradiation environments when combined with other solid lubricants.Secondly， the challenges faced by solid lubricating films in irradiation environments were summarized， and an outlook on future research directions in the field of radiation resistance of commonly used solid lubricating films was provided.Five strategies to enhance the radiation resistance of solid lubricating films were further explored:First，thermal annealing treatments were conducted，after which two-dimensional layered lubricating films，such as MoS2，were shown to exhibit fewer defects when subjected to irradiation.Second，doping with radiation-resistant elements was proposed；for example，chromium was introduced into carbon-based lubricating films，effectively improving the tribological stability and durability of DLC materials.The third strategy involved designing multilayer film structures that captured defect atoms through heterointerfaces， effectively improving the tribological performance of metal-based lubricating films.The fourth strategy was to regulate the interfacial area，where the crystal/amorphous interface was found to have higher radiation tolerance.The fifth strategy was to refine the grain size， as grain refinement was shown to effectively improve the radiation resistance of metal-based lubricating films.In conclusion，solid lubricating thin films have great application potential in extreme environments such as space exploration and the nuclear industry.Future research will focus on deeply understanding the impact of irradiation on solid lubricating thin films and developing new strategies to improve their radiation resistance， ensuring that these materials can maintain their excellent lubricating performance in extreme environments.